Pengelolaan Dana Desa sebagai Upaya Meningkatkan Pemberdayaan Masyarakat Desa Basseang Kabupaten Pinrang - Taswin Taswin; Adriani Adriani; Hasliah Hasliah; Rahman Pance (Yayasan Literasi Sains Indonesia, 2026)
This study aims to determine how Village Fund management is carried out in Basseang Village, Lembang District, Pinrang Regency, and to what extent it contributes to increasing community empowerment. This research uses a qualitative approach with a descriptive type. Data collection techniques were conducted through in-depth interviews, observation, and documentation studies. Informants in this study consisted of village officials, the Village Consultative Body (BPD), community leaders, and Village Fund beneficiaries. The results showed that Village Fund management in Basseang Village still focuses on physical development, while community empowerment programs have not received adequate attention. Community participation in program planning and implementation is still low, and supervision of the use of the Village Fund has not been optimal. The empowerment programs that have been carried out, such as skills training and small business assistance, are still limited and have not had a significant impact on increasing the economic independence of the community. In conclusion, the management of the Village Fund in Basseang Village has not fully supported community empowerment efforts as a whole. Therefore, it is necessary to increase community participation, program planning that is more oriented to local needs, and strengthen the capacity of village officials and community institutions so that the Village Fund truly becomes a tool for social transformation.